Recent Progress of Two-Dimensional Transition Metal Dichalcogenides for Thermoelectric Applications - Zhou, Wei; Gong, Huimin; Jin, Xiaohe; Chen, Yang; Li, Huimin; Liu, Song (Frontiers in Physics, 2022)
Two-dimensional transition metal dichalcogenides (2D-TMDs) have sparked immense interest, resulting from their unique structural, electronic, mechanical, and thermal properties. The band structures, effective mass, electron mobility, valley degeneracy, and the interactions between phonons and heat transport properties in 2D-TMDs can be efficiently tuned via various approaches. Moreover, the interdependent electrical and thermal conductivity can be modulated independently to facilitate the thermoelectric (TE)-based energy conversion process, which enables optimization of TE properties and promising TE applications. This article briefly reviews the recent development of TE properties in 2D-TMDs. First, the advantages of 2D-TMDs for TE applications are introduced. Then, the manipulations of electrical and thermal transport in 2D-TMDs are briefly discussed, including various influencing factors such as thickness effect, structural defects, and mechanical strain. Finally, the recent advances in the study of electrical, thermal transport, and TE properties of 2D-TMDs, TE-related applications, the challenges, and the future prospects in this field are reviewed.